2008
DOI: 10.1111/j.1468-1331.2008.02087.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation of serum uric acid levels in multiple sclerosis during relapses and immunomodulatory treatment

Abstract: Uric acid (UA), a product of purine metabolism, may be an antioxidant, perhaps acting as a scavenger of peroxynitrite. Patients with gout have a reduced incidence of multiple sclerosis (MS). A number of studies found that patients with MS have low serum levels of UA, although it has not been established whether this represents a primary deficit or a secondary effect. UA has also been proposed as a marker of disease activity and response to immunosuppressive or immunomodulatory treatment. We retrospectively rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Three studies were published in Chinese, while others were in English. Three studies [14][15][16] were excluded due to no original data reported, while another three studies [17][18][19] were excluded because they were reviews. For consistency, we included studies of only case-control design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies were published in Chinese, while others were in English. Three studies [14][15][16] were excluded due to no original data reported, while another three studies [17][18][19] were excluded because they were reviews. For consistency, we included studies of only case-control design.…”
Section: Resultsmentioning
confidence: 99%
“…8,11,22,23 In this review, we have also demonstrated a trend towards serum UA levels were lower in patients with MS than in healthy controls and OINDs. Serum UA levels were inverse correlation with MS. On the basis of these findings, we could speculate that lower serum UA reserve is possibly an early pathogenic mechanism in MS. Additionally, the pathogenetic role of UA in MS is also supported by data showing the significant increase in serum UA in patients receiving interferon-beta or glatiramer-acetate, which have been shown to reduce disease activity in MS. 24,25 It is generally accepted that lower serum UA in MS patients might be due to both intrinsically reduced antioxidant capacity and increased consumption of UA in MS. However, we have to admit the fact that the potential association between serum UA levels and the clinical status in MS is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between urate levels and clinical and paraclinical disease activity and disability has been also evaluated, with conflicting results [9], [11], [13], [15], [19], [21], [25], [26], [36] Consistently with the results of the metanalysis, [28] in our study serum urate did not correlate with disability level and disease duration, but lower urate levels were observed in female patients with higher disease activity (ARR) and in the early phases (CIS) of the MS. Based on these findings the contribute of inadequate protection against reactive oxygen and peroxynitrite by urate to the axonal loss and the clinical progression of the disease still remains uncertain, but a role of low urate in favouring neuroinflammation and demyelination that occur early in MS and mainly in females may be hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed lower levels of serum uric acid in MS patient s (7,11,22,23,25), and also Mattle et al (25) reported that uric acid levels were decreased in MS patients when compared to control subjects along with in patients with relapse were lower than in patients in remission. Serum UA levels were lower in the mono-and dizygotic twins with MS than in the healthy twin (7).…”
Section: Discussionmentioning
confidence: 96%